Carl Sagan: a exploração e colonização de planetas - ficção científica,cência e divulgação - Souza, Carlos A. Loiola de (2006)
Sci - fi books depending on how they are structured by their authors, might be in our case, the astronomer Carl Sagan, be used as reference texts in Science History by his indisciplinity. The specific case of interplanetary trips, theorized and thought scientificaly and advertised under a sci - fi language in books of Carl Sagan, is what this dissertation talks about.The authors of fiction texts, such as Sagan Arthur Charles Clarke and Issac Asimov, try to found their extrpolate in careful notes of trends that happen in society and science, and develop the ( narration, in Asmov and Clarke´s case ) implication or advertising with rigidity and consistency.On the other hand, part of the futuristic literature would be an important History of Science analysis instrument, for it to be possible of thinking in alternative proposals for a scientific policy and taught which may have a social reach. A kind of experiment or imaginary exercise. In other words, what is studied here, is the relation between sci - fi and science, which talks about interplanetary trips, and how they are explained in Sagan´s books. However, the dissertation, delimitates, in the first instance, must be considered about interplanetary trips, its dissimilation from the 30´s to the 60´s and the adverstising through two of the best sci - fi writers of the twentieth century, whose work was to advertise scientific ideas or Astronautic for a better understanding of the science, its role and the impact of science and technology, in a society which moves really fast, but without many details. After all, as it was a relevant realization of some of these realized fantasies by Carl Sagan´s commitment, initially, with the American industial military complexduring the Cold War against USSR, and after that by NASA.And what we have learned scientifically from the exploration of the Solar Sistem and the nearest planets, in a way that the results of this spacial exploration could be advertised with the help from literature and fiction, in a type of alert about the problems that we will have to face in a near future. At last, the mankind destiny, imagined by Sagan in a kind of manifest advertised by himself in his main books and analysed here for it to be possible to keep its parallelism of contents and trends between sci - fi books and the academic literatureabout the development of science and technology and the destiny of mankind and the individuals that make itself. This is a conclusion that History students having a beginning or complementary graduation in humanities, will be able to find on the shelves of science history, a worthy manifest for an unexpective reflection or for a militancy